VAKSINASI BCG MENINGKATKAN AKTIVITAS FAGOSITOSIS DAN SEKRESI REACTIVE OXYGEN INTERMEDIATE (ROI) PADA MAKROFAG PERITONEUM KUCING YANG DIINFEKSI DENGAN Mycobacterium tuberculosis - Tjahajati, Ida (Fakultas Kedokteran Universitas Brawijaya, 2005)
ABSTRACT The aim of this experiment was to study the effect of BCG vaccination on phagocyte activity and ROI secretion in cat peritoneum macrophages which infected with M.tuberculosis. The experiment used twenty four healthy cats. The animals were divided in 2 groups, 12 cats in each group. Group I were vaccinated with BCG, group II were control group which unvaccinated. BCG vaccination was done twice in two weeks interval. Two days after vaccination each cat was infected by 105 cfu M.tuberculosis intraperitoneally. The activity of macrophages were measured at 1st, 2nd, 12th, and 24th, after infection using in vitro latex bead phagocyte and NBT reduction assay. Three cats were used to measure the macrophage activity in each period, using triplicate sample for each cat. The results of the experiment showed that the phagocyte activity and ROI secretion increased significantly in vaccination group (P<0.01) compared with the control group, and these activities reached to the plateau level at 2 weeks after infection. Although these enhanced activities were gradually diminished thereafter, higher levels of these activities were consistently observed until the end of experiment compared with control group. BCG vaccination increased the cellular immunity especially phagocyte and ROI secretion activities of peritoneual macrophages in cat infected with M.tuberculosis Key words: BCG, phagocyte, ROI, M.tuberculosis, cat